Pembrolizumab-induced cytokine release syndrome in a patient with metastatic lung adenocarcinoma: a case report - Chul Kim; Paul Sackstein; Jacob Zaemes (Journal for ImmunoTherapy of Cancer)
Cytokine release syndrome (CRS) is a well-described immune-related adverse event following chimeric antigen receptor T-cell therapy, but has rarely been reported following anti-programmed death ligand-1 therapy. We report the case of a 55-year-old man with metastatic lung adenocarcinoma who presented with fever, chills and hypotension. Initial labs were notable for highly elevated serum ferritin levels and mildly elevated triglyceride levels. He was ultimately diagnosed with pembrolizumab-induced CRS complicated by multiorgan failure. The patient was treated with steroids and tocilizumab with normalization of inflammatory markers and resolution of renal failure. This case not only highlights the importance of considering CRS in patients who have developed multiorgan failure after immune checkpoint inhibitor therapy, but also demonstrates clinical similarities between CRS and other hyperinflammatory states such as hemophagocytic lymphohistiocytosis.